Okkupation : Symposium. - Arlt, Peter; Baumann, Leonie; Hasucha, Christian; Jonas, Uwe; Knobloch, Andrea; Reuter, Martina; Schamp, Matthias; Schumacher, Birgit Anna (Berlin : Schumacher & Jonas Berlin, 2004)
Hasucha, Christian ; Gerken, Ingo ; Hertzsch, Eva ; Page, Adam ; Niscino, Tazro ; ILAP ; Vaara, Roi ; Kellndorfer, Veronika ; Böhm, Kathrin ; Lang, Andreas ; Saffer, Stefan ; Knobloch, Andrea ; Schamp, Matthias ; Winkler, Hans ; Jonas, Uwe ; Schumacher, Birgit Anna
Geboortedatum per kunstenaar
boek